2020
DOI: 10.1186/s13000-020-01037-4
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage multi-differentiated gastric carcinosarcoma and post-resection local recurrence: a case report

Abstract: Background Carcinosarcoma is a rare neoplasm with a poor prognosis that is most often discovered at an advanced stage; a gastric carcinosarcoma is even rarer than carcinosarcomas originating in other organs, such as the uterus. We report our experience with an early-stage multi-differentiated gastric carcinosarcoma. Case presentation A 68-year-old male patient presented with anemia, and his fecal occult blood test was positive. An endoscopic examination was conducted which revealed a hemorrhagic, irregular, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The prognosis for patients with carcinosarcoma remains quite poor, with a mean survival period estimated to be 7–10 months, with 50% of recurrences occurring within the first year postoperatively [ 12 ]. To our knowledge, only 6 cases [ 1 , 4 , 13 – 15 ], including ours, have been diagnosed at an early stage thus far. Interestingly, 4 of the 6 cases showed regional lymph node metastasis, demonstrating the aggressive nature of this tumor.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The prognosis for patients with carcinosarcoma remains quite poor, with a mean survival period estimated to be 7–10 months, with 50% of recurrences occurring within the first year postoperatively [ 12 ]. To our knowledge, only 6 cases [ 1 , 4 , 13 – 15 ], including ours, have been diagnosed at an early stage thus far. Interestingly, 4 of the 6 cases showed regional lymph node metastasis, demonstrating the aggressive nature of this tumor.…”
Section: Discussionmentioning
confidence: 93%
“…Carcinosarcoma is a rare, malignant, and biphasic tumor that has aspects of both carcinoma (a cancer of epithelial tissue) and sarcoma (a cancer of connective tissue). It is often of müllerian origin and arises in the uterus, ovary, and fallopian tube, but it has also been reported to occur in the esophagus, thyroid, lungs, larynx, breasts, and urinary tract [ 1 , 2 ]. While already rare, carcinosarcoma of the gastric mucosa is much rarer, with a literature review citing fewer than 100 reported cases of gastric carcinosarcoma [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carcinosarcoma is an aggressive malignant tumour composed of epithelial and mesenchymal components. It is usually metastasised to other organs at the time of diagnosis 1. It is frequently referred to as sarcomatoid and spindle cell carcinoma of the stomach.…”
Section: Introductionmentioning
confidence: 99%